Inflammatory Differences in Plaque Erosion and Rupture in Patients With ST‐Segment Elevation Myocardial Infarction. Issue 5 (May 2017) - Chandran, Sujay; Watkins, Johnathan; Abdul‐Aziz, Amina; Shafat, Manar; Calvert, Patrick A.; Bowles, Kristian M.; Flather, Marcus D.; Rushworth, Stuart A.; Ryding, Alisdair D.
Abstract : Background: Plaque erosion causes 30% of ST‐segment elevation myocardial infarctions, but the underlying cause is unknown. Inflammatory infiltrates are less abundant in erosion compared with rupture in autopsy studies. We hypothesized that erosion and rupture are associated with significant differences in intracoronary cytokines in vivo. Methods and Results: Forty ST‐segment elevation myocardial infarction patients with <6 hours of chest pain were classified as ruptured fibrous cap (RFC) or intact fibrous cap (IFC) using optical coherence tomography. Plasma samples from the infarct‐related artery and a peripheral artery were analyzed for expression of 102 cytokines using arrays; results were confirmed with ELISA. Thrombectomy samples were analyzed for differential mRNA expression using quantitative real‐time polymerase chain reaction. Twenty‐three lesions were classified as RFC (58%), 15 as IFC (38%), and 2 were undefined (4%). In addition, 12% (12 of 102) of cytokines were differentially expressed in both coronary and peripheral plasma. I‐TAC was preferentially expressed in RFC (significance analysis of microarrays adjusted P <0.001; ELISA IFC 10.2 versus RFC 10.8 log2 pg/mL; P =0.042). IFC was associated with preferential expression of epidermal growth factor (significance analysis of microarrays adjusted P <0.001; ELISA IFC 7.42 versus RFC 6.63 log2 pg/mL, P =0.036) and thrombospondin 1 (significance analysis of microarrays adjusted P =0.03; ELISA IFC 10.4 versus RFC 8.65 log2 ng/mL, P =0.0041). Thrombectomy mRNA showed elevated I‐TAC in RFC ( P =0.0007) epidermal growth factor expression in IFC ( P =0.0264) but no differences in expression of thrombospondin 1. Conclusions: These results demonstrate differential intracoronary cytokine expression in RFC and IFC. Elevated thrombospondin 1 and epidermal growth factor may play an etiological role in erosion.